2020
DOI: 10.1007/978-3-030-45771-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Sparsity over Lattices and Semigroups

Abstract: Motivated by problems in optimization we study the sparsity of the solutions to systems of linear Diophantine equations and linear integer programs, i.e., the number of non-zero entries of a solution, which is often referred to as the ℓ 0 -norm. Our main results are improved bounds on the ℓ 0norm of sparse solutions to systems Ax = b, where A ∈ Z m×n , b ∈ Z m and x is either a general integer vector (lattice case) or a non-negative integer vector (semigroup case). In the lattice case and certain scenarios of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 23 publications
4
21
0
Order By: Relevance
“…In the knapsack case m = 1, the bound (5) strengthens Theorem 1.2 in [3] and, as it was already indicated in the IPCO version of this paper [1], it confirms a conjecture posed in [3, page 247]. Moreover, as a byproduct of the proof of Theorem 2 we obtain the following algorithmic result.…”
Section: Bounds For Icr(a) and Icc(a)supporting
confidence: 86%
See 1 more Smart Citation
“…In the knapsack case m = 1, the bound (5) strengthens Theorem 1.2 in [3] and, as it was already indicated in the IPCO version of this paper [1], it confirms a conjecture posed in [3, page 247]. Moreover, as a byproduct of the proof of Theorem 2 we obtain the following algorithmic result.…”
Section: Bounds For Icr(a) and Icc(a)supporting
confidence: 86%
“…It is however not clear if it is possible to adapt this approach for the case of the 0 objective. This motivates the following problem: (1) and the functions ILR(A), ILC(A), ICR(A) and ICC(A) be computed in pseudo-polynomial time, i.e., when the input numbers are given in unary encoding rather than binary?…”
Section: Theoremmentioning
confidence: 99%
“…This is closely related to the results on the sparsity of systems of linear Diophantine equations in [2].…”
supporting
confidence: 59%
“…If c = 0 n , then σ(b) quantifies the sparsest feasible solution to IP(b). Upper bounds on σ(b) under this assumption were studied in [2,6]. Furthermore, Oertel et al [31] showed that asymptotic densities of σ can be bounded using the minimum absolute determinant of A or the 'number of prime factors' of the determinants.…”
mentioning
confidence: 99%
“…Bounds of this type are dated back to the classical integer Carathéodory theorems of Cook, Fonlupt and Schriver [10] and Sebő [17]. More recent contributions include results of Eisenbrand and Shmonin [12] and Aliev et al [1,2,3]. Further, in a very recent work Lee, Paat, Stallknecht and Xu [15] apply new sparsity-type bounds to refine the bounds for proximity.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%